2020
DOI: 10.1590/0034-7167-2019-0300
|View full text |Cite
|
Sign up to set email alerts
|

Content Translation And Validation Of The Pediatric PIV Infiltration Scale Into Brazilian Portuguese

Abstract: Objectives: to translate, adapt and validate the PIV Infiltration Scale content into Brazilian Portuguese. Methods: a methodological study. Initial translation was performed by two bilingual translators, translation synthesis; backtranslation to the original language; elaboration of the translated version and adapted by expert consensus; content validation and pretest. Results: the Pediatric PIV Infiltration Scale has been translated and adapted. Discrepancies were sorted out by consensus. The scale content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The algorithm also evaluated the clinical severity of the complication based on a scale adapted for children and called “ Pediatric PIV Infiltration Scale ”, recently translated and adapted to Brazilian Portuguese ( 30 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithm also evaluated the clinical severity of the complication based on a scale adapted for children and called “ Pediatric PIV Infiltration Scale ”, recently translated and adapted to Brazilian Portuguese ( 30 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In grade 2, mild edema (up to ¼ or from 10% to 25% of the extremity above or below the insertion site), hyperemia and pain at the site can be identified. Regarding grade 3, moderate edema (¼ to ½, or 25%-50% of the extremity above or below the insertion site), pain at the site, cold skin to the touch, pallor at the site, and pulse decreased below the site can be observed; and, in grade 4, edema classified as severe (more than ½ or 50% of the extremity above or below the insertion site), cold skin to the touch, pallor at the site, skin rupture/necrosis, blistering, decreased or absent pulse, pain at the site and capillary filling > 4 seconds ( 30 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The scale, translated into Brazilian Portuguese and ready for use, are attached to this article. In this process, it is necessary to adapt the language for the target population from a cultural and conceptual standpoint, while maintaining the objective of the original instrument (20) . The specialist committees had an agreement represented by a CVI of 1.00 in 93.48% of the questions, a being within values recommended in literature for committees made up by seven judges (13) .…”
Section: Domain 5: Publication and Professional Leadershipmentioning
confidence: 99%
“…The Brazilian version of the EMDF/EPA scale was submitted to a pre-test, which aims to maintain the meaning of the original version, improve understanding, and to find mistakes and/or problems in the application of the instrument being adapted (20) . The results of the pre-test of the scale showed that, in spite of the changes carried out in the content validation stage, by recommendation of the evaluative committee, there were no discrepancies in understanding, and high scores were reached.…”
Section: Domain 5: Publication and Professional Leadershipmentioning
confidence: 99%
“…It is an extremely painful procedure, and a stressful experience for newborns, children and family members. In the context of care, the maintenance of PIC should follow protocols that promote the safety of neonatal and pediatric patients, as well as the durability of venous access for as long as possible [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%